THE INFLUENCE OF WATER HARDNESS AND DIETARY CALCIUM ON GROWTH AND SURVIVAL OF POSTLARVAL PRAWN,, Macrabrachium rosenbergii - M. Fatuchri Sukadi (Indonesian Fisheries Research Journal, 1999)
The influence of water hardness on survival of freshwater prawn, Macrobrachiumrosenbergii was investigated in indoor tanks during a 132-day study.